Change in forced vital capacity and associated subsequent outcomes in patients with newly diagnosed idiopathic pulmonary fibrosis. Issue 1 (December 2015) - Reichmann, William; Yu, Yanni; Macaulay, Dendy; Wu, Eric; Nathan, Steven
Abstract Background Idiopathic pulmonary fibrosis (IPF) is a rare and serious disease characterized by progressive lung-function loss. Limited evidence has been published on the impact of lung-function loss on subsequent patient outcomes. This study examined change in forced vital capacity (FVC) across IPF patients in the 6 months after diagnosis and its association with clinical and healthcare resource utilization (HRU) outcomes in a real-world setting in the U.S. Methods A retrospective chart review was conducted of patients diagnosed with IPF by U.S. pulmonologists. Patient eligibility criteria included: 1) 40 years or older with a confirmed date of first IPF diagnosis with high-resolution computed tomography and/or lung biopsy between 01/2011 and 06/2013; 2) FVC results recorded at first diagnosis (±1 month) and at 6 months (±3 months) following diagnosis. Based on relative change in FVC percent predicted (FVC%), patients were categorized as stable (decline <5 %), marginal decline (decline ≥5 % and <10 %), or significant decline (decline ≥10 %). Physician-reported clinical and HRU outcomes were assessed from 6 months post-diagnosis until the last contact date with the physician and compared between FVC% change groups. Multivariable Cox proportional-hazards models were constructed to assess risk of mortality, suspected acute exacerbation (AEx), and hospitalization post-FVC% change. Generalized estimating equations were used to account for multiple patients contributed by individual physicians. Results The sample included 490 IPF patients contributed by 168 pulmonologists. The mean (SD) age was 61 (11) years, 68 % were male, and the mean (SD) baseline FVC% was 60 % (26 %). 250 (51 %) patients were categorized as stable, 98 (20 %) as marginal decline, and 142 (29 %) as significant decline. The mean (SD) observation time was 583 (287) days. In both unadjusted analysis and multivariable models, significantly worse clinical outcomes and increased HRU were observed with greater lung-function decline. Conclusions These findings suggest that nearly half of IPF patients experienced decline in FVC% within 6 months following IPF diagnosis. Greater FVC% decline was associated with an increased risk of further IPF progression, suspected AEx, mortality, and higher rate of HRU. Management options that slow FVC decline may help improve future health outcomes in IPF.